Laboratory experiments on diffusive convection layer thickness and its oceanographic implications. Issue 10 (14th October 2016) - Guo, Shuang‐Xi; Zhou, Sheng‐Qi; Qu, Ling; Lu, Yuan‐Zheng
Abstract: We studied the thickness of diffusive convective layers that form when a linearly stratified fluid is subjected to heating from below in the laboratory. The thickness of the bottom convecting layer is much larger than subsequent layers. These thicknesses are systematically identified and used to examine the available convecting layer thickness parameterizations, which are consisted of the measured heat flux F (or thermal buoyancy flux qT ), initial stratification N, density ratio Rρ, thermal diffusivity κT, etc. Parameterization with an intrinsic length scale ( q T 3 κ T N 8 ) 1 / 4 is shown to be superior. Including the present laboratory convecting layer thicknesses and those observed in oceans and lakes, where layer thickness ranges from 0.01 to 1000 m, the parameterization is updated as H = C ( R ρ − 1 ) 2 ( q T 3 κ T N 8 ) 1 / 4, where C = 38.3 for the bottom convective layer and 10.8 for the subsequent layers. Different prefactors are proposed to be attributed to different convective instabilities induced by different boundary conditions. Key Points: The thicknesses of the bottom and subsequent convecting layers can be represented by the same combination of physical variables of different prefactors The modified layer thickness parameterization can describe the diffusive convecting layer occurring in the laboratory as well as in oceans and lakes